Comparative analysis reveals the contribution of phage-derived genomic islands to the increasing pathogenicity of facultative bacterial pathogens - Poly, Israt Jahan Khan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.